The Role of Amodal Surface Completion in Stereoscopic Transparency - Anderson, Barton; Schmid, Alex (Frontiers in Psychology, 2012)
Previous work has shown that the visual system can decompose stereoscopic textures into percepts of inhomogeneous transparency. We investigate whether this form of layered image decomposition is shaped by constraints on amodal surface completion. We report a series of experiments that demonstrate that the stereoscopic depth differences are easier to discriminate when the stereo images generate a coherent percept of surface color, than in images that require amodally integrating a series of color changes into a coherent surface. Our results provide further evidence for the intimate link between the segmentation processes that occur in conditions of transparency and occlusion, and the interpolation processes involved in the formation of amodally completed surfaces.